Endovascular revascularization for aortoiliac atherosclerotic disease - Aggarwal, Vikas (Vasc Health Risk Manag, 2016)
Atherosclerotic iliac artery disease is increasingly being treated with endovascular techniques. A number of new stent technologies can be utilized with high long-term patency, including self-expanding stents, balloon-expandable stents, and covered stents, but comparative data on these stent types and in more complex lesions are lacking. This article provides a review of currently available iliac stent technologies, as well as complex procedural aspects of iliac artery interventions, including approaches to the treatment of iliac bifurcation disease, long segment occlusions, choice of stent type, and treatment of iliac artery in-stent restenosis.